Exploring Lexical Semantics: A Comparative Study of English and a Natural Language - Dr. Shahab Ahmad Al Maaytah; Joseph Philip Ayobami; Dr. Ibrahim abdelfattah Almajali (Al-Qanṭara, 2025)
This article examines the relationship between semantics in English and the (Natural language) Yorùbá language, emphasizing how lexical meanings are constructed and interpreted in both linguistic contexts. By utilizing natural language examples, the study highlights the complexities of word meanings and their variations across languages. It begins with an overview of semantic theories and the significance of lexical semantics, followed by an exploration of how specific English terminologies can be understood within the Yorùbá language framework. This research not only aims to formalize these semantic connections but also contributes to the understanding of bilingualism and the dynamics of meaning in multilingual settings.